Faith, Knowledge, and Charity: Communication and Implementation in University Life / Iman, Ilmu, dan Amal: Komunikasi dan Implementasinya dalam Kehidupan Universitas - Zikri Fachrul Nurhadi; Dian Ranita; Ummu Salamah (Alhadharah: Jurnal Ilmu Dakwah, 2024)
This research is motivated by the results of a survey on the understanding of the motto "Faith, Knowledge, Charity" at Garut University, which only reached 15.4% of the academic community. From a communication perspective, this raises concern for the researcher, as meaning is the substance of the ongoing communication process. The aim of this research is to explain the motto "Faith, Knowledge, Charity" from the aspects of motivation, experience, and meaning. The research method used is a descriptive method with a qualitative approach. Data collection techniques include observation, in-depth interviews, literature study, and documentation. Research subjects were selected using purposive sampling, with a total of 11 informants and 3 sources. The results show that the motive for using the motto "Faith, Knowledge, Charity" is the founders' desire to transform the entire academic community of Garut University into beneficial human beings, a field for good deeds, and a source of motivation to achieve the goals of Garut University. The communication experience can be seen in the implementation of the motto through worship to God, doing good deeds to others, and the execution of functions by each element at Garut University. The meaning contained in the motto serves as a foundation for the academic community to carry out every activity, functioning as a motivational drive and a form of responsibility towards the social environment, applied both on campus and in society, to realize the vision, mission, and goals of Garut University.